Enhancement of structural and dielectric properties of PVC/CNC nanocomposites as electrical insulation materials - Nurul Shafiqah Amirah, Badi; Mohamad Zul Hilmey, Makmud; Zuhair, Jamain; Khairatun Najwa, Mohd Amin; Hazlee Azil, Illias (SAGE Publications Ltd, 2024)
This work aims to introduce bio-based nanocomposite as high voltage electrical insulation material by using cellulose nanocrystal (CNC) isolated from filter paper as a filler of polymer matrix, in this case, polyvinyl chloride (PVC). CNC is obtained via acid hydrolysis treatment and incorporated into PVC by using the casting method at different concentrations. The structural and thermal characterization have been investigated using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The dielectric properties as a function of the alternating current (AC) sinusoidal frequency of PVC/CNC were examined by the electrical impedance spectroscopy (EIS) test method. Breakdown voltage tests according to the ASTM D149 standard were conducted to determine the dielectric strength of nanocomposites. Hence, the results indicate that the addition of CNC by 1 wt% is the best formulation to improve the base polymer structure, in this case PVC, as well as its dielectric insulation properties.